Effect of single bout versus repeated bouts of stretching on muscle recovery following eccentric exercise - Torres, R.; Pinho, F.; Duarte, J. A.; Cabri, J. M. H. (Journal of Science and Medicine in Sport, 2013)
Objectives: To analyze the effects of a single bout and repeated bouts of stretching on indirect markers of exercise-induced muscle damage. Design: A randomized controlled clinical trial at a university human research laboratory was conducted. Methods: Fifty-six untrained males were randomly divided into four groups. (I) a single stretching group underwent a single bout of stretching on the quadriceps muscle; (II) an eccentric exercised group underwent eccentric quadriceps muscle contractions until exhaustion; (III) an eccentric exercise group followed by a single bout of stretching; (IV) an eccentric exercised group submitted to repeated bouts of stretching performed immediately and 24, 48, and 72 h post-exercise. Muscle stiffness, muscle soreness, maximal concentric peak torque, and plasma creatine kinase activity were assessed before exercise and 1, 24, 48, 72, and 96 h post-exercise. Results: All exercised groups showed significant reduction in maximal concentric peak torque and significant increases in muscle soreness, muscle stiffness, and plasma creatine kinase. There were no differences between these groups in all assessed variables, with the exception of markers of muscle stiffness, which were significantly lower in the eccentric exercise group followed by single or repeated bouts. The single stretching group showed no change in any assessed variables during the measurement period. Conclusions: Muscle stretching performed after exercise, either as single bout or as repeated bouts, does not influence the levels of the main markers of exercise-induced muscle damage; however, repeated bouts of stretching performed during the days following exercise may have favorable effects on muscle stiffness.